Profile analysis and functional modeling identify circular RNAs in nonalcoholic fatty liver disease as regulators of hepatic lipid metabolism - Xie, Yang; Cao, Yi; Guo, Can-Jie; Guo, Xing-Ya; He, Ya-Fang; Xu, Qing-Yang; Shen, Feng; Pan, Qin (Frontiers in Genetics, 2022)
Nonalcoholic fatty liver disease (NAFLD) is the leading cause of chronic liver disease, associated with an outcome of hepatic fibrosis/cirrhosis and hepatocellular carcinoma. However, limited exploration of the underlying mechanisms hinders its prevention and treatment. To investigate the mechanisms of epigenetic regulation in NAFLD, the expression profile of circular RNA (circRNA) of rodents in which NAFLD was induced by a high-fat, high-cholesterol (HFHC) diet was studied. Modeling of the circRNA-microRNA (miRNA) -mRNA regulatory network revealed the functional characteristics of NAFLD-specific circRNAs. The targets and effects in the liver of such NAFLD-specific circRNAs were further assessed. Our results uncovered that the downregulation of 28 annotated circRNAs characterizes HFHC diet-induced NAFLD. Among the downregulated circRNAs, long intergenic non-protein coding RNA, P53 induced transcript (LNCPINT) -derived circRNAs (circ_0001452, circ_0001453, and circ_0001454) targeted both miR-466i-3p and miR-669c-3p. Their deficiency in NAFLD abrogated the circRNA-based inhibitory effect on both miRNAs, which further inactivated the AMPK signaling pathway via AMPK-α1 suppression. Inhibition of the AMPK signaling pathway promotes hepatic steatosis, depending on the transcriptional and translational upregulation of lipogenic genes, such as those encoding sterol regulatory element-binding protein 1 (SREBP1) and fatty acid synthase (FASN) in hepatocytes. The levels of LNCPINT-derived circRNAs displayed a negative association with hepatic triglyceride (TG) concentration. These findings suggest that loss of LNCPINT-derived circRNAs may underlie NAFLD via miR-466i-3p- and miR-669c-3p-dependent inactivation of the AMPK signaling pathway.